ISO 45001 standard: Opportunity for healthcare organizations to improve occupational health - Torres-Mendoza , Karina Elizabeth (2022)
The present study has the general purpose of analyzing the ISO 45001 Standard as an opportunity for health organizations to improve occupational health. The methodology corresponds to an investigation of a documentary nature and a descriptive level. For the collection of information sources, the Internet database of specialized academic information sites and reliable sources was used. The analysis sample was made up of 07 literary sources compiled because they considered that they were the ones that most precisely adjusted the interests of this study. From this, the content analysis of the information collected was carried out. The results found show that there are weaknesses in the study contexts addressed in the analysis units for the implementation of an SG-SST, based on the requirements demanded by the ISO 45001 Standard. It is concluded that the implementation of the ISO 45001 Standard, It can contribute to occupational health and safety since the requirements contemplated in this regulatory body are adapted to any type of organization regardless of its size and nature, since its main objective is the prevention of accidents at work.